Of blood and sweat : Black lives and the making of White power and wealth - Ford, Clyde W. (Amistad, an imprint of HarperCollins Publishers, 2022)
"Of Blood and Sweat: Black Lives and the Genesis of White Power and Wealth tells the story of how Black lives and labor created White power and wealth in agriculture, politics, jurisprudence, law enforcement, culture, medicine, financial services, and other fields. Through the lives of individual Black men and women a deeper understanding unravels of the role Blacks played, directly and indirectly, in creating American institutions of power and wealth-while never allowed full participation. Today, activists have taken the struggle for racial equity and justice to the streets. Of Blood and Sweat depicts this struggle from pre-colonial Africa through post-Civil War America and a consistent theme emerges: Trace the history of almost any major American institution of power and wealth and you'll find it was created by Black Americans, or created to control them. Painstakingly researched, and comprehensively documented, Of Blood and Sweat is a compelling look at the past with broad implications for present-day calls for racial equity, racial justice, and the abolishment of systemic racism"--